Analysis of the Relationship between Nutritional Status and Stress with the Menstrual Cycle in Adolescent Girls - Aisyah, Iseu Siti; Neni, Neni; Muharry, Andy (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The causes of menstrual cycle irregularities in adolescents are multifactorial, including nutritional status and stress levels. Irregular menstrual patterns, if left unaddressed, may have long-term implications for reproductive health. This study aimed to analyze the association between nutritional status and stress levels with menstrual cycle patterns in 127 adolescent girls aged 13–15 years from three private junior high schools within the service area of Bantar Community Health Center, Tasikmalaya City. A cross-sectional design was employed. Nutritional status was assessed using anthropometric measurements, stress levels were evaluated through the DASS questionnaire, and data on menstrual cycle regularity and intervals were collected via a structured questionnaire. Chi-square analysis indicated a significant correlation between nutritional status and menstrual cycle patterns (p-value = 0,027), with adolescents experiencing malnutrition showing a higher proportion of menstrual irregularities compared to those with normal nutritional status. Fisher’s exact test also demonstrated a significant association between stress levels and menstrual cycle patterns (p-value = 0,043), with adolescents exhibiting high stress levels having an increased risk of menstrual cycle disturbances. These findings underscore that imbalanced nutritional status and elevated stress levels can disrupt hormonal function and compromise menstrual cycle regularity in adolescent girls. Therefore, monitoring nutritional status and implementing stress management strategies are essential to support regular menstrual cycles and promote reproductive health in this population.